Punjabi Ghazal of “The Ravi” Magazine - Latif, Wasif; Bukhari, Syed Ghazanfar Hussain; Wattoo, Subha Sadiq (sourcecoder, 2023)
Government College Lahore was established in 1864 while the first literary magazine "The Ravi" was started in January 1906 which was published monthly. The publication of Punjabi literature in "The Ravi" began with folk songs. Later, a series of essays, stories, editorials, satire and poetry began, which continues to this day. Like Punjabi language and literature, various prose and poetic genres have been published in the magazine "Ravi". Ghazal is not a Punjabi genre but has come from Persian to Urdu and Punjabi. In "The Ravi" has published less Ghazals than other genres, but Ghazals have been published in satisfactory numbers along with other genres. This research article discusses the Punjabi Ghazal of "The Ravi" and tries to bring to the fore the tradition and themes of Punjabi Ghazal from the beginning.